2018
DOI: 10.4103/jfmpc.jfmpc_114_18
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of physical activity with body image, self esteem sedentary lifestyle, body mass index and eating attitude in adolescents: A cross-sectional observational study

Abstract: Aim:To Study Relationship of physical activity (PA) with body image, self-esteem, body mass index (BMI), sedentary lifestyle and eating attitude in adolescents.Methods:An observational cross-sectional study done at the Centre for Adolescent Health, Kalawati Saran Children Hospital, Lady Hardinge Medical College, New Delhi, India. Volunteering adolescents between the age group of 13 and 18 years were included and assessed using PA questionnaire for adolescents Score, Body Shape Questionnaire-34 Score, Rosenberg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 19 publications
(14 reference statements)
1
6
0
Order By: Relevance
“…Higher physical activity was associated with better physical and mental QOL in this study, corroborating previous results [ 32 ]. In fact, physical activity increases positive emotions such as interest, excitement, and enthusiasm., enhances positive moods by increasing pleasant, energized feelings, increases muscles strength and the ability to function properly [ 32 , 64 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Higher physical activity was associated with better physical and mental QOL in this study, corroborating previous results [ 32 ]. In fact, physical activity increases positive emotions such as interest, excitement, and enthusiasm., enhances positive moods by increasing pleasant, energized feelings, increases muscles strength and the ability to function properly [ 32 , 64 ].…”
Section: Discussionsupporting
confidence: 93%
“…Body image education increase self-esteem and reduce body dissatisfaction [ 31 ]. Likely, physical activity (PA) has a positive effect on body image and is associated with body image improvement [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, in our study, it was observed that as the physical activity levels of the students increased, their muscle strength satisfaction also increased. In a study conducted with adolescents, an increase in sedentary lifestyle among students participating in the study was associated with a decrease in body image scores [ 37 ]. In another study on Norwegian university students indicated that female students studying sports science had higher body appreciation scores compared to other departments [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed the relationship between a decrease in physical activity in adolescents and an increase in sedentary behavior, which is particularly associated with the availability of technology-based activities during leisure time (Gaddad et al, 2018). In the United States, 71% of teenagers have access to more than one social networking website, and 24% use the Internet almost continuously with mobile phones.…”
Section: Sedentary Behaviors Among Adolescentsmentioning
confidence: 93%
“…Increasing sedentary behaviors and decrease in physical activity are also the main drivers of the global obesity pandemic (Blüher, 2019). Unfortunately, research findings have shown that young people engage in too little physical activity, eat unhealthily, and spend too much time sitting (Gaddad, Pemde, Basu, Dhankar, & Rajendran, 2018;Kantanista et al, 2020). Regular participation in high-quality physical education activities is critical for shaping positive habits, establishing interest in physical activity, and compensating the time spent in the sitting position among adolescents.…”
Section: Introductionmentioning
confidence: 99%